Determination of Success Driven Motivation in Communication for Secondary Education 10th Year Students TRNC Sample - Terkan, Remziye; Ucar, Onder (International Review of Management and Marketing, 2021)
The goal of this research is to determine the Success Driven Motivation in Communication of year 10 high school students. In this research the screening model has been used in order to determine opinions of participants. The study has been designed as a karma model that incorporates both quantitative and qualitative research models. In order to analyse data descriptive statistics such as frequency, percentage, arithmetic mean, and standard deviation and the Mann Whitney U- and Kruskal Wallis H- tests have been used. During the study “the case study” method has been employed as a qualitative research model. This research has been conducted over the second term of the 2020-2021 educational year in the Turkish Republic of Northern Cyprus. In accordance with the goals of this research a personal information form and semi structured meeting form have been used. This research has been undertaken in 2020-2021 academic year. The sampling for this research has been determined by applying the research on year 10 students from randomly selected state high schools under the Ministry of Education of North Cyprus in 2 districts, 50 students in Nicosia and 51 students in Famagusta (101 total). Keywords: Secondary students, motivation driven communication, motivation JEL Classification: D83 DOI: https://doi.org/10.32479/irmm.10905